Randomized Controlled Trial on Effect of Intermittent Early Versus Late Kangaroo Mother Care on Human Milk Feeding in Low-Birth-Weight Neonates. (August 2017) - Jayaraman, Dhaarani; Mukhopadhyay, Kanya; Bhalla, Anil Kumar; Dhaliwal, Lakhbir Kaur
Background: Breastfeeding at discharge among sick low-birth-weight (LBW) infants is low despite counseling and intervention like kangaroo mother care (KMC). Research aim: The aim was to study the effects of early initiation of KMC on exclusive human milk feeding, growth, mortality, and morbidities in LBW neonates compared with late initiation of KMC during the hospital stay and postdischarge. Methods: A randomized controlled trial was conducted in level 2 and 3 areas of a tertiary care neonatal unit over 15 months. Inborn neonates weighing 1 to 1.8 kg and hemodynamically stable were randomized to receive either early KMC, initiated within the first 4 days of life, or late KMC (off respiratory support and intravenous fluids). Follow-up was until 1 month postdischarge. Outcomes were proportion of infants achieving exclusive human milk feeding and direct breastfeeding, growth, mortality and morbidities during hospital stay, and postdischarge feeding and KMC practices until 1 month. Results: The early KMC group ( n = 80) achieved significantly higher exclusive human milk feeding (86% vs. 45%, p < .001) and direct breastfeeding (49% vs. 30%, p = .021) in hospital and almost exclusive human milk feeding (73% vs. 36%, p < .001) until 1 month postdischarge than the late KMC group ( n = 80). The incidence of apnea (11.9% vs. 20%, p = .027) and recurrent apnea requiring ventilation (8.8% vs. 15%, p = .02) were significantly reduced in the early KMC group. There was no significant difference in mortality, morbidities, and growth during the hospital stay and postdischarge. Conclusion: Early KMC significantly increased exclusive human milk feeding and direct breastfeeding in LBW infants.